Search for CP violation in the decays D±→K0SK±, D±s→K0SK±, and D±s→K0Sπ± - Lees, Jean-Pierre; Adametz, Aleksandra; Uwer, Ulrich (Physical review. D, Particles, fields, gravitation, and cosmology, 2013)
We report a search for CP violation in the decay modes D±→K0SK±, D±s→K0SK±, and D±s→K0Sπ± using a data set corresponding to an integrated luminosity of 469 fb−1 collected with the BABAR detector at the PEP-II asymmetric energy e+e− storage rings. The decay rate CP asymmetries, ACP, are determined to be (+0.13±0.36(stat)±0.25(syst))%, (−0.05±0.23(stat)±0.24(syst))%, and (+0.6±2.0(stat)±0.3(syst))%, respectively. These measurements are consistent with zero, and also with the Standard Model prediction [(−0.332±0.006)% for the D±→K0SK± and D±s→K0SK± modes, and (+0.332±0.006)% for the D±s→K0Sπ± mode]. They are the most precise determinations to date.
Im Titel ist das Plus-Minus und die Zahl 0 hochgestellt
Im Titel ist der Buchstabe "S" (großes S und kleines s) tiefgestellt
Gesehen am 18.11.2021